The Influence of Supervisor and Co-Worker Social Support Towards Resilient Self-Efficacy of Psychiatric Hospital Nurses - Tasia Puspa Sari; Jenny Lukito Setiawan (Faculty of Psychology, Universitas Gadjah Mada, 2020)
The standard and complexity of nurse job tend to create heavy burden for nurses in performing nursing duties. The current study aimed to examine the influence of social support from supervisors and co-workers towards the resilient self-efficacy of psychiatric hospital nurses. The participants were 70 psychiatric hospital nurses in Surabaya. The study used Social Support Scale and Resilient Self-efficacy Scale. Multiple linear regression analysis showed that supervisor and co-worker support simultaneously had a significant influence on psychiatric hospital nurses’ resilient self-efficacy (F = 32.837; p<0.05) with contribution of 35% (R2 = 0.3528). Hypothesis testing showed that when given separately, supervisor social support did not influence psychiatric hospital nurses’ resilient self-efficacy (r=0.089; p > 0.05). However, co-worker social support significantly influenced psychiatric hospital nurses’ resilient self-efficacy even when given separately (r=0.558; p < 0.05). This study concluded that compared with supervisor social support, co-worker social support significantly influenced psychiatric hospital nurses’ resilient self-efficacy.